Information visualization for the lod services on national R&D data - Jeong, Hanjo; Ki Kim, Yong; Park, Minwoo (International Journal of Engineering and Technology, 2018)
Background/Objectives: NTIS (National Science & Technology Information Service) is constructed and operated to provide a comprehensive data-provider service of national R&D data. Thus, NTIS is needed to manage and share the national R&D data in a more open and standardized way.Methods/Statistical analysis: This paper presents a lightweight ontology-based LOD service and its visualization interfaces on the national R&D data maintained by NTIS. The lightweight ontology is used to represent the information and the knowledge of the R&D data in terms of the information entities and their simple relationships.Findings: The lightweight ontology enables us to process the R&D data in more semantic and efficient ways. For the visualizations, a hierarchical and network-type user interfaces are introduced to represent the NTIS LOD data and allow users to browse the LOD data in a more convenient way. This research also presents the overall system architecture of the NTIS LOD system.Improvements/Applications: The hierarchical and network visualization interfaces effectivenessly represent the LOD data, and also allow users to search and browse the LOD data in more convenient and efficient ways.Â